PENGARUH DUKUNGAN SPIRITUAL TERHADAP KUALITAS HIDUP PENDERITA KANKER PAYUDARA PASCA KEMOTERAPI - Yusniarita, Yusniarita (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
The Rejang Lebong district prevalence of breast cancer in women of reproductiveage or premenopausal compare with women who had menopause also affects of treatmentsuch as chemotherapy and lack of family support in the from of spiritual support couldinfluence quality of the life of patients. The purpose of this study to determine the effect ofspiritual support to the quality of life of breast cancer patients post chemotherapy at RejangLebong district. Metode Quasi Experiment One Group Pre dan Post Test. The was population33 and sampel was 12 respondents. There are differnences in the quality of research results tosupport the spiritual life of breast cancer patients after chemotherapy in Rejang lebong district2014. This discusstions are expected to patients in order to inprove the quality of life andspiritual breast cancer patients for example thorough spiritual activities such as recitation andfor health workers in order to conduof health education about breast cancer